IMPLEMENTASI MEDIA JAMBOARD PADA MATA KULIAH BAHASA INDONESIA DI MASA PANDEMI DI UNIVERSITAS BATTUTA (STUDI KASUS PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR) - Dewi Sartika Panggabean; Zulvia Misykah (Universitas Negeri Medan, 2022)
This study will explore the Google Jamboard learning method during covid-19 during online learning, showing that the perception of students and lecturers regarding the most effective application when online learning is using Google Jamboard?. The purpose of this study is to see learning media that can support student success based on the teaching and learning process as an effective form of activity in order to achieve the desired goals, it is hoped that learning media will become a mediator which is one of the tools in the teaching and learning process. The expected result after the implementation of this research is to increase the knowledge and understanding of students and lecturers in Indonesian language courses. This study will look at the effect of using Google Jamboard on the effectiveness of the learning process in Indonesian language courses in the elementary school teacher education study program at Battuta University. After the results of this study, in the future, students and lecturers during online learning, lecturers will certainly find it easier to provide Indonesian language course material to students by using Google Jamboard.